Influência do diâmetro de dois pinos de fibra de vidro transfixados horizontalmente sobre a resistência à fratura de dentes endodonticamente tratados - Fávero, Fernando José (2013)
Objectives: 1) To assess the fracture strength of cavity preparations, directly restored with composite resin, with and without the presence of fiberglass posts with different diameters; 2) to assess the fracture pattern of cavity preparations, restored or not, with or without the presence of fiberglass posts with different diameters. Materials and Methods: Eighty-four extracted third molars were embedded in acrylic resin and divided into 6 groups (n = 14 per group): healthy (H); cavity preparation (P); cavity preparation + endodontic treatment (PE); PE + composite resin (R); PE + R + 2 horizontally transfixed fiberglass posts 1.1 mm in diameter (PERP1); PE + R + 2 fiberglass posts 1.5 mm in diameter (PERP2). The MOD cavity preparations were standardized with their width corresponding to 2/3 of the buccolingual distance and occlusogingival depth of 4 mm, with 2 mm remaining above the cementoenamel junction. Endodontic treatments were performed in the PE, R, PERP1 and PERP2 groups. The buccal surface received two demarcations to create orifices for placement of the PERP1 and PERP2 posts. Once the fiberglass posts were placed, the teeth were restored with composite resin. In group R, only composite resin was used. After 24 h, the teeth were subjected to the fracture toughness test on a universal testing machine EMIC DL – 2000. A 10KN load cell and crosshead speed of 1 mm/min were used until fracture occurred. After testing, the teeth were inspected for the type of fracture classified as: pulpal floor fracture (AP) or cuspal fracture (CP). Results: The data were subjected to ANOVA and Tukey’s test (P<0.05%), demonstrating a statistical difference between groups: H 3,830NA; P 778ND; PE 572.93ND; R 1,782NC; PERP1 2,988NB; PERP2 3,100NAB. The fracture pattern was similar between the tested groups, showing 50% of fracture for cusps and pulpal floor. Conclusions: The use of 2 fiberglass posts with different diameters, restored with composite resin, recovered around 80% of the fracture strength of a healthy tooth.